2011
DOI: 10.1186/1758-5996-3-15
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence in type 2 diabetes patients - first results from a feasibility study of the D2C cohort

Abstract: BackgroundA large prospective study in patients with type 2 diabetes (T2D), the German D2C cohort, is presently being enumerated to investigate risk factors of incident cancer in diabetic patients.Study settingA disease management program was offered, on a voluntary basis, to all T2D patients who were members of a statutory health insurance fund in Germany. This first feasibility report uses data from 26.742 T2D patients, who were 40 to 79 years old, resided in the Muenster District, and who were enrolled betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 16 publications
4
28
0
3
Order By: Relevance
“…The risk was also most influential in the younger age group making it reasonable to suspect that this may be attributable to metabolic dysfunction preceding DM diagnosis. Concurrently to previous findings, results from prospective cohort study on German population (26, total of 742 subjects) showed an increased risk of cancer with SIR 1.14 (95% CI; 1.10–1.21), but the duration of diabetes was inversely associated with the cancer risk which was markedly higher within the first year after diabetes diagnosis [43]. …”
Section: Epidemiologysupporting
confidence: 61%
“…The risk was also most influential in the younger age group making it reasonable to suspect that this may be attributable to metabolic dysfunction preceding DM diagnosis. Concurrently to previous findings, results from prospective cohort study on German population (26, total of 742 subjects) showed an increased risk of cancer with SIR 1.14 (95% CI; 1.10–1.21), but the duration of diabetes was inversely associated with the cancer risk which was markedly higher within the first year after diabetes diagnosis [43]. …”
Section: Epidemiologysupporting
confidence: 61%
“…The association between the use of metformin and the risk of any malignancy was described in 25 studies recruiting 579,621 patients, 7 RCTs (17,785 patients) [24,44,64,65,67,69], and 18 observational studies (561,836 patients) [25-27,30,33,36,37,46,47,50,51,53,55,57,62,70,71,73] (Figure 2B). …”
Section: Resultsmentioning
confidence: 99%
“…In addition, we excluded patients who were on TZD and/or insulin to better assess the association between metformin and PCa risk by eliminating potential confounding effects of other glucose-lowering medications that could themselves have an effect on PCa incidence or progression, as reported in the literature (3133). …”
Section: Methodsmentioning
confidence: 99%